Structural, transport and optical properties of (La0.6Pr0.4)0.65Ca0.35MnO3 nanocrystals: A wide band-gap magnetic semiconductor - Kumar S.; Dwivedi G.D.; Kumar S.; Mathur R.B.; Saxena U.; Ghosh A.K.; Joshi A.G.; Yang H.D.; Chatterjee S. (My University, 2025)
(La0.6Pr0.4)0.65Ca0.35MnO3 system has been synthesized via a sol-gel route at different sintering temperatures. Structural, transport and optical measurements have been carried out to investigate (La0.6Pr0.4)0.65Ca0.35MnO3 nanoparticles. Raman spectra show that Jahn-Teller distortion has been decreased due to the presence of Ca and Pr in A-site. Magnetic measurements provide a Curie temperature around 200 K and saturation magnetization (MS) of about 3.43μB/Mn at 5 K. X-ray photoemission spectroscopy study suggests that Mn exists in a dual oxidation state (Mn3+ and Mn4+). Resistivity measurements suggest that charge-ordered states of Mn3+ and Mn4+, which might be influenced by the presence of Pr, have enhanced insulating behavior in (La0.6Pr0.4)0.65Ca0.35MnO3. Band gap estimated from UV-Vis spectroscopy measurements comes in the range of wide band gap semiconductors (∼3.5 eV); this makes (La0.6Pr0.4)0.65Ca0.35MnO3 a potential candidate for device application. This journal is © The Royal Society of Chemistry 2015.